Perencanaan Teknis Rehabilitasi Ruas Jalan Tirtayasa ( Studi Kasus Simpang Antasari - Simpang Sutami) - Kusnadi, Kusnadi; Diana, I Wayan; Purba, Aleksander (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2019)
Road is an infrastructure of land transportation which is very important for the growth of life because the road is a link between one region to another. In its use, the road always carries heavy loads every time someone crosses it so that it will be vulnerable for damage to occure  at the road surface and pavement structure.One effort to prevent more serious damage to the road is by conducting road rehabilitation such as patching and overlay thickness with the aim of restoring pavement strength so as to provide optimal service to road users. For this reason, a road rehabilitation plan is needed so that it is able to withstand the traffic load that passes through the road and has the as planned age.The purpose of this study was to determine the level of road damage on the Tirtayasa road section. To find out the method of improvement that can be done based on the level of damage and to find out the costs needed to repair the Tirtayasa road.This study begins with data collection and road damage conditions such as groove depth of cracks and holes resulting from visual survey.Analysis of the road conditions based on SDI values, for the Tirtayasa road along 4.8 km, with good conditions (75%), moderate conditions 0.4 km (6.25%), mildly damaged conditions 1.2 km (18, 75%), and 0 km (0%) is severely damaged, so that rehabilitation is done in the form of patching and overlay and the overlay and patching on the Road segment Tirtayasa needs a budget of Rp. 3,254,555,000.00Keywords: planning, technical road rehabilitation